Women’s Resilience in Ecological Crisis: An Ecofeminist Perspective on Women Affected by the Lapindo Mudflow - Iva Yulianti Umdatul Izzah; Ries Dyah Fitriyah; Afifatur Rohimah; Nihlatul Falasifah; Novie Andriani Zakariya (Millati: Journal of Islamic Studies and Humanities, 2025)
Climate change and ecological disasters have significant impacts on women’s lives, particularly in the context of the Lapindo mudflow. This study aims to uncover the resilience experiences of women affected by the disaster, their strategies in coping with the crisis, and the role of gender in public policy. The research employs a qualitative approach with an ecofeminist perspective to highlight the social, economic, health, environmental, cultural, and spiritual experiences of affected women. Analysis was conducted to examine the resilience strategies implemented, ranging from strengthening social solidarity, engaging in microeconomic activities, maintaining health, managing the environment, to practicing cultural and spiritual traditions. The findings indicate that: (1) women face complex disaster impacts, including loss of homes, forced relocation, social dislocation, difficulties in accessing public services, psychosocial pressures, and disruption of education and traditional practices; (2) women’s resilience strategies encompass social, economic, health, environmental, as well as cultural and spiritual aspects; (3) the study also found gender exclusion in decision-making and village deliberations, resulting in women’s voices often being marginalized; (4) the study recommends full participation of women in recovery processes and disaster policy formulation to ensure greater equity and inclusivity.